Numerical simulation of gas dispersion during cold venting of natural gas pipelines - Ning Liao; Kun Huang; Liqiong Chen; Zhifang Wang; Jin Wu; Fang Zhang (Advances in Mechanical Engineering, 2018)
This article analyzes the effects of various factors on gas dispersion during cold venting based on the actual cold venting operations of long-distance natural gas pipelines in China. Under the circumstance that no obstacles existed, unified dispersion model and PHAST software were used to simulate the gas dispersion process of cold venting in order to study the changes of gas concentration along vertical and horizontal directions over time. FLUENT was used to make numerical simulations to analyze the effect of the existence of high obstacles on gas dispersion. The results indicated that (1) with an increase in wind speed, the concentration range in which the gas might explode (5%–15%) decreased along the vertical direction but slightly increased along the horizontal direction; (2) when the initial venting pressure gradually decreased with the proceeding of cold venting, the downwind distance that might trigger danger reduced significantly; and (3) with an increase in atmospheric stability, the dispersion height of vented gas first increased and then decreased continuously. High atmospheric stability could inhibit the gas dispersion height to a larger degree than the wind speed and aerostatic buoyancy could facilitate it.